AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN COMPREHENDING NARRATIVE TEXT AT GRADE X FASHION DESIGN SMK NEGERI 1 KISARAN IN 2023-2024 ACADEMIC YEAR - Aliya Shafira; Melly Andani Widodo (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This research aims to analyze the difficulties faced by students in understanding reading narrative texts in class X TB 1 SMK NEGERI 1 KISARAN. Using qualitative methods and a descriptive approach, this research involved 34students as subjects. Data was collected through in-depth interviews, classroom observations, and analysis of learning documents. The research results showed that students experienced various difficulties, including limited vocabulary, lack of effective reading strategies, and inability to understand the structure and plot of the story. Apart from that, students' motivation and interest factors also play a significant role in the reading comprehension process. These findings provide important insights for educators to design more adaptive and innovative teaching strategies, in order to improve students' reading comprehension abilities. Thus, it is hoped that this research can become a reference in efforts to improve the quality of Indonesian language learning, especially in the context of narrative texts.